The Effect of the Performance of Micro and Small Companies on the Collectability with Spirituality as Moderating Variable - Adi Kuswanto; Maulana Ali (Conference In Business, Accounting, And Management (CBAM), 2012)
The government provides a variety of aids to micro and small companies in order to increase the competitiveness of them and their performance and in return their collectability The objectives of the research are (a) to explore and analyze the effect of the performance of micro and small companies on the collectability?; and (b) to explore and analyze the moderation of the spirituality on the relationship between the performance of micro and small companies and their collectability. The location of the research is at southern sumatera and the number of samples are 250 micro and small companies. We use 2 independent varables (ROI and spirituality) and a dependent variable (collecatbility). The results show that the micro and small companies (debtors of PT Pertamina) have increased their performance measured by return on investment (ROI). Their performance do not affects on the collectability. As the owners of micro and small companies have and applicate the spirituality knowledges, the performance of micro and small companies influence on the collectability.Keywords: Performance, spirituality, and collectability.